DINAMIKA PERIKANAN TUNA LONG LINE INDONESIA (STUDI KASUS TUNA SIRIP BIRU SELATAN) - Novia Tri Rahmawati; Sugeng Hari Wisudo; Eko Sri Wiyono; Tri Wiji Nurani (Fakultas Perikanan dan Ilmu Kelautan, 2013)
As the member of Commission for The Conservation of Southern Bluefin Tuna (CCSBT), Indonesia shall follow the quota measure of SBT fishing that has determined. Therefore, good management and rules were needed for SBT exploitation in Indonesia in order to align with measures and international regulation that has agreed by Indonesia as part of CCSBT. The objectives of this research wereto determine catch composition, productivity of Indonesia tuna longline fisheries especially that doing SBT fishing activity; to estimatesfishing season; and to determine mean size at capture of SBT in Indonesia. Theresult showedthat catch composition of tuna longline has the smallest percentage value for the type of SBT. Trend of SBT production percentage was increase every year in 19 years period. Fishing season of SBT in Indonesia was in August to March that assumed same with nursery season of SBT. Mean size at capture of SBT (L50%)was 145 cm FL. This size that assumed has feasible to be caught or has beyond spawning period.